1995
DOI: 10.3382/ps.0740176
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Effects of Rigor Mortis-Accelerating Treatments in Broiler Pectoralis

Abstract: This study was conducted to elucidate the mechanism of action of two selected rigor mortis-accelerating treatment systems employed in the prevention of the toughness associated with early-harvested (1 h post-mortem) broiler Pectoralis muscle. The treatments included 14 min of low voltage electrical stimulation (110 V, 1 A, pulsing 1 s on and 1 s off) combined with high temperature conditioning (39 C) and muscle tensioning (LV + HTC + MT); a 15-s high voltage stimulation (440 V, 1 A pulsing 2 s on and 1 s off) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…As a result, Etherington et al (1987) postulated that the rapid rate of conditioning in the avian species may account for differences in proteolytic activity from mammalian muscle. Walker et al (1995) found that residual µ-calpain activity in Pectoralis was absent at 24 hr post-mortem suggesting complete autolysis by this time.…”
Section: Structural and Biochemical Changes Associated With Postmortementioning
confidence: 95%
See 2 more Smart Citations
“…As a result, Etherington et al (1987) postulated that the rapid rate of conditioning in the avian species may account for differences in proteolytic activity from mammalian muscle. Walker et al (1995) found that residual µ-calpain activity in Pectoralis was absent at 24 hr post-mortem suggesting complete autolysis by this time.…”
Section: Structural and Biochemical Changes Associated With Postmortementioning
confidence: 95%
“…The activities of µand m-calpain were determined using the extraction and caseinolytic methods described by Wheeler and Koohmaraie (1990). Myofibrillar protein extraction using modified procedures described by Walker et al (1995) enabled the detection of the 30 kDa protein. The procedure was modified in order to concentrate myofibrillar proteins by homogenizing muscle samples in 2.5 volumes of extraction buffer instead of the 6 volume.…”
Section: Structural and Biochemical Changes Associated With Post-mortmentioning
confidence: 99%
See 1 more Smart Citation
“…While broilers have a high-voltage ES decreased at least m-calpain activity "p-calpain was completely autolysis in both ES and control muscles" (Walker et al 1995). ES, on the other hand, enhanced calpain activity but had no impact on m-calpain (Alvarado and Sams 2000).…”
Section: Resultsmentioning
confidence: 96%